2021
DOI: 10.3390/horticulturae8010032
|View full text |Cite
|
Sign up to set email alerts
|

Quali-Quantitative Study on Phenol Compounds as Early Predictive Markers of Graft Incompatibility: A Case Study on Chestnut (Castanea spp.)

Abstract: In recent years, research has focused on phenolic compounds and their putative role as markers of graft incompatibility. Thus far, no studies have been conducted on the role of phenolic compounds in chestnut (Castanea spp.). The present study investigated the content of phenolic compounds in different combinations of Castanea spp. cultivars and rootstocks. Analyses were performed on the inner and outer tissues of chestnut grafts at two phenological sampling stages. The separation, identification and quantifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 25 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…These indicated that the regulation of the metabolites in the bud on the grafting growth was significantly different among varieties. Because phenols (anthocyanins, flavanones, p-coumaric acid, and hydroxybenzoic acid) and (±)catechins have a significant effect on grafting ( Hudina et al., 2014 ; Dinc et al., 2018 ; Elsheery et al., 2020 ; Gamba et al., 2021 ), we hypothesized that the metabolic composition of the buds could be one of the key factors determining seedling growth.…”
Section: Resultsmentioning
confidence: 99%
“…These indicated that the regulation of the metabolites in the bud on the grafting growth was significantly different among varieties. Because phenols (anthocyanins, flavanones, p-coumaric acid, and hydroxybenzoic acid) and (±)catechins have a significant effect on grafting ( Hudina et al., 2014 ; Dinc et al., 2018 ; Elsheery et al., 2020 ; Gamba et al., 2021 ), we hypothesized that the metabolic composition of the buds could be one of the key factors determining seedling growth.…”
Section: Resultsmentioning
confidence: 99%